Antibiotic Application and Resistance in Swine Production in China: Current Situation and Future Perspectives - Yang, Hong; Paruch, Lisa; Chen, Xunji; van Eerde, André; Skomedal, Hanne; Wang, Yanliang; Liu, Di; Liu Clarke, Jihong (Frontiers in Veterinary Science, 2019)
To meet increasing demand for animal protein, swine have been raised in large Chinese farms widely, using antibiotics as growth promoter. However, improper use of antibiotics has caused serious environmental and health risks, in particular Antimicrobial resistance (AMR). This paper reviews the consumption of antibiotics in swine production as well as AMR and the development of novel antibiotics or alternatives in China. The estimated application of antibiotics in animal production in China accounted for about 84240 tons in 2013. Overuse and abuse of antibiotics pose a great health risk to people through food-borne antibiotic residues and selection for antibiotic resistance. China unveiled a national plan to tackle antibiotic resistance in August 2016, but more support is needed for the development of new antibiotics or alternatives like plant extracts. Antibiotic resistance has been a major global challenge, so international collaboration between China and Europe is needed.